On the spectral relations for multitime correlation functions - Shvaika, A.M. (Condensed Matter Physics, 2006)
A general approach to the derivation of the spectral relations for the multitime correlation functions is presented. A special attention is paid to the consideration of the non-ergodic (conserving) contributions and it is shown that such contributions can be treated in a rigorous way using multitime temperature Green functions. Representation of the multitime Green functions in terms of the spectral densities and solution of the reverse problem, i.e., finding the spectral densities from the known Green functions, are given for the case of the three-time correlation functions.